2005
DOI: 10.1088/0022-3727/38/16/005
|View full text |Cite
|
Sign up to set email alerts
|

Diode laser measurements of the Ar 3p54s1excited states in an inductively coupled RF plasma

Abstract: Diode laser absorption spectroscopy has been used to study the four lowest energy excited states of atomic argon (1s2–1s5) arising from the 3p54s1 electronic configuration and produced in an inductively coupled RF discharge. Three of the states (1s2, 1s4 and 1s5) were detected using wavelength modulation spectroscopy with diode laser radiation in the wavelength range 425–430 nm, obtained by frequency doubling the output of a near infrared diode laser in a KNbO3 crystal. The 1s3 state was probed using direct ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…k m = 3.7 × 10 −14 exp(−15 eV/k B T e ) m 3 s −1 [25] for the excitation to the metastable state and k i = 2 × 10 −13 exp(−5 eV/k B T e ) m 3 s −1 [25] for the ionization and k t = 2 × 10 −13 m 3 s −1 [25] for the transfer to the resonant state of metastable atoms by electron impact. The radiative lifetime of the resonant Ar * ( 3 P 1 ) state is a few nanosecond; however, due to resonant radiation trapping, the effective radiative lifetimes reach a few microsecond and consequently the density of Ar * ( 3 P 1 ) atoms becomes almost comparable to that of the metastable state [26,27] and consequently the reverse process (electron impact transfer from 3 P 1 to 3 P 2 ), which has 5/3 times larger rate coefficient, partly compensates the depletion of the Ar * ( 3 P 2 ) state. Therefore, the overall depletion rate by population transfer must be smaller than k t .…”
Section: Resultsmentioning
confidence: 99%
“…k m = 3.7 × 10 −14 exp(−15 eV/k B T e ) m 3 s −1 [25] for the excitation to the metastable state and k i = 2 × 10 −13 exp(−5 eV/k B T e ) m 3 s −1 [25] for the ionization and k t = 2 × 10 −13 m 3 s −1 [25] for the transfer to the resonant state of metastable atoms by electron impact. The radiative lifetime of the resonant Ar * ( 3 P 1 ) state is a few nanosecond; however, due to resonant radiation trapping, the effective radiative lifetimes reach a few microsecond and consequently the density of Ar * ( 3 P 1 ) atoms becomes almost comparable to that of the metastable state [26,27] and consequently the reverse process (electron impact transfer from 3 P 1 to 3 P 2 ), which has 5/3 times larger rate coefficient, partly compensates the depletion of the Ar * ( 3 P 2 ) state. Therefore, the overall depletion rate by population transfer must be smaller than k t .…”
Section: Resultsmentioning
confidence: 99%
“…In low pressure plasmas, the measured [Ar(1s3)]/[Ar(1s5)] density ratio was usually closer to 0.1 63,64,65,66 , rather than to the statistical value (2J3+1)/ (2J5+1)=0.2, where J3=0 and J5=2 are the total angular momentum of 1s3 and 1s5 sates, respectively. The observed enhancement of this ratio with increasing argon pressure, reaching 0.3 at atmospheric pressure, can be related to both smaller reaction coefficient of Ar*(1s3) atoms in 3-body collision with 2 Ar atoms (Eq.…”
Section: On Relative Peak Densities Of Metastable Atomsmentioning
confidence: 91%
“…8 for a surfatron plasma with the same radius, in which the n(1s 3 )/n(1s 5 ) ratio was rising from 0.1 at 0.26 millibars to 0.35 at 3.7 millibars. Bakowski et al 35 also reported a density ratio near 0.1 in an ICP plasma source. For the n(1s 4 )/n(1s 5 ) ratio, one observes a small deviation from the predicted statistical equilibrium.…”
Section: Densities Of Ar(4 S) Atomsmentioning
confidence: 91%